ANALISIS HISTOLOGI GINJAL IKAN BAUNG (Hemibagrus nemurus) YANG TERINDIKASI PENCEMARAN DI PERAIRAN SUNGAI KAMPAR PROVINSI RIAU - ', Erlangga (Berkala Perikanan Terubuk, 2011)
Several large and small rivers in Riau flow down into the estuary ofKampar River. Water that flown from these resources, however, may containmany types of pollutants as there are many industrial and domestic activitiesconducted along the river dispose their waste in the river. The present of thepollutant strongly affect the water quality and negatively affect aquatic organismliving in the river. To understand the effects of the pollutant, especially theindustrial pollutant on the biology of aquatic organisme, this study wasconducted. Samples of water, sediment and Hemibagrus nemurus (Bagridae) weretaken and the presence of heavy metal in these samples were analyzed. Heavymetal content in the sediment and water were analyzed using an AAS method,while its presence in the fish was detected in the kidney that was processed forhistological analysis. Results shown that the highest Pb and Cd content waspresent in the kidney of fish living in the downstream, followed by fish living inthe midstream and the lowest was in the fish captured in the upstream.Histological analysis of the kidney shown that there is abnormality of the kidneytissue as there are necrotic cells, limphocyte presence, infected glomerulus andhaemorrhagic spots. Heavy metals accumulation was also detected as there areblack spots (indication of heavy metal mineralization) present in that tissue. Aswell as in the fish tissue, the highest heavy metal content were found in the waterand sediment taken from the downstream, followed by mid and downstream.However, statistical analysis shown that there is no interaction between Cdcontent and sampling sites (P>0.05). Data obtained in this research proved that thewaste originated from industrial activities along the river negatively affect waterquality as well as aquatic organisms, especially Bagridae fish.